Impact of community care services on the health of older adults: evidence from China - Ma, Wenjing; Shen, Zheng (Frontiers in Public Health, 2023)
Introduction: The rapid growth in the population of older adults has put tremendous pressure on medical and social services in countries including China. Community care services are a feasible solution for promoting healthy aging in developing countries. This study investigated the association between community care services and the health of older adults in China. Method: Using a nationally representative survey data in China, we employed linear regression models with time fixed effects and instrumental variable approaches to estimate the effect of community care services on the health of older adults, as well as the differences of these effects across sub groups. Results: The results showed that community care services lead to a significant improvement in the health and well-being of older adults. Among the various service offerings, the effects were most pronounced for spiritual recreation and medical care services, which can significantly extend active aging and improve well-being, implying a different effect of subdivided service types. Further evidence suggests that spiritual recreation services have a significant health-enhancing effect on multiple groups of older adults, and the effect of medical care services is more effective for those living in rural areas, females, and those that are older than 80 years. Discussion: Few studies have examined the impact of community care services on the health of older adults in developing countries. The findings present important implications for improving the health status of older adults and provide suggestions for establishing a socialized aged care system in China and other developing countries.